Correspondence: the donation of human milk during the COVID-19 pandemic - Pasqua Anna Quitadamo (Hygeia Press di Corridori Marinella, 2020)
Dear Editor, In previous epidemics, it has been shown that the use of breast milk represents one of the first crucial measures to be taken in emergencies. On the occasion of the World Day for the Donation of Human Milk, which was celebrated on May 22, the Italian Society of Neonatology (SIN) reaffirmed the importance of Human Milk Banks (HMBs), reassuring mothers about the safety of donation at HMBs, also in this pandemic period. In the Neonatal Intensive Care Unit (NICU) of San Giovanni Rotondo, Italy, we found that the restrictive measures did not represent a reason to limit breastfeeding nor donation. We have been close to nursing and donating mothers, providing constant support from the HMB and NICU staff, with practical advice and psychological closeness. In particular, in the February-May period, the crucial one of the pandemic, 15 donors donated 91.25 liters. In comparison with the average of previous years of donation data to the HMB, the balance is even in favor of the current year. In fact, in 2019, in the same period, 12 mothers were recruited and 58.7 liters were collected and, in 2018, the donor women were 10 but they donated 119.5 liters. As manager of the HMB, I found it useful to report the experience of our HMB and our NICU on this specific aspect, and I hope that other HMBs can do the same. I believe that these testimonies can represent an element of hope, encouragement and reflection. Solidarity did not end with the lockdown.